The optical text in the cinema film Between the presence and absence Play for free mark: حسام الدين محمد عبد المنعم (Al-Academy, 2016)
The light-based life in the universe, including the human derived concepts and meanings of the fear of darkness and evil, comfort and goodness of light, became constitute bilateral haunted man to this day in various concepts of life.Therefore reflect the light form artistic aesthetic in visual arts such arts Fine Photography and the other until the emergence of art cinema, as the use of lighting in cinema has produced high-energy in the composition of its values expressive and symbolic, where it became dark and light are the space visually moving the vehicles media kit for many within the work structure artwork. The research is divided into five chapters, the first chapter (the methodological framework) that included an introduction the problem of the research was to ask the following (you can have light text in the structure of the artwork as a system function of practice Alamati? And what refers to the text of photosynthesis in the film, the atmosphere, or deepen the event, or deepen the general meaning of the film?). And the importance of research and the need him as well as the objective of this research as well as to clarify the limits of search and search terms. The second chapter has included the theoretical framework and previous studies and the Department of the theoretical framework from two sections the first / text photosynthesis as a system media kit. The second chapter / text photosynthesis and play for free brand. Then we but applications that are adopted by the researcher to analyze the selected sample and to reach the goal of his research included the approach adopted in the research and the reasons for selecting the samples and the search tool and unit of analysis. Then the analysis of the sample consisted And draw the final results emanating from the analysis was highlighted that the mark is subject to employment maker of work and as well as display some of continuous movement has and where it occurs in context, as well as view some of the conclusions derived from the search results also included Some of the recommendations that the researcher deems necessary, as well as proposals for further studies, and research has included a list of sources and references that are adopted by the researcher is also available in Arabic and foreign study and a summary in English